Islam And State In Seventeenth Century Aceh - Amirul Hadi (McGill Univercity, 1999)
ABSTRACT The present dissertation studies the islamic nature of the Acehnese stare in the seventeenth century -a subject much neglected by area scholars and islamicists alike due to the hybrid natrue of Southeast Asian Isiam. It examines not only the state's Islamic institulions but also its political culturne and policies towards Islam- The Acehnese theory of kingship during the period under study manifests a decidedly Islamic character. Deemed tro possess both political and religious auhority, the office of ihe suhan was viewed as oecessary and its incumbent responsible for both the prosperity of his people and tbe enforcement of islamic dogrna- The court's policies towards Islam, given outward expression in elaborate religious rituals and ceremonies. reveal an imperial tradition in which the ruler himself was the head of the Muslim state, despite the apparent admixture of Southeasi Asian elements. Other more traditional islamic institutions were also fundamental to the Acehnese state. The 'ulama' played a significant role in both the religious and political spheres, while Islamic law became a dominant part of the judicial system alongside adat (customary law and royal edicts/tradition). Jihad as well served to define the ideology of the state. ln spite of its Southeast Asian appearance, therefore, the Islnmic nature of the Acehnese state was more evident than in many other Muslim ststes in the region, such as fifteenth-century Melaka and seventeenth century Mataram, a situation induced by geography, historical Islam. and the nature of Acehnese tradition.